Social support, grit, and academic stress among MBKM students - Aurelia Vania Diastari; Andik Matulessy (School of Tourism, Universitas Ciputra Surabaya, 2026)
Since its implementation in 2020, the Merdeka Belajar - Kampus Merdeka (MBKM) program has produced both positive and negative impacts on students. It enhances soft skills, cognitive abilities, social competence, scientific literacy, and problem-solving skills. However, it also creates challenges such as time management difficulties, limited communication with lecturers, and increased physical and mental fatigue, which contribute to rising academic stress. Initial data from 78 students showed an average academic stress score of 42.4 for non-participants, while MBKM participants reached 51.1. This study aims to assess the predictive role of social support and grit on academic stress in MBKM students. A total of 224 students from various regions in Indonesia participated in this quantitative study. Analysis was conducted using multiple linear regression in SPSS. The results showed that social support and persistence were significantly related to academic stress (0.000 < 0.05), with F = 48.472 (greater than F table = 3.09) and R² = 0.305. This means that 30.5% of the variation in academic stress can be explained by social support (4.69%) and persistence (25.8%). The regression coefficients of social support (-0.225) and persistence (-0.866) indicate that an increase in both factors is associated with a decrease in academic stress. Overall, this study concludes that persistence is a stronger predictor of academic stress in MBKM students.